Beginner's guide to candlemaking - Constable, David (Search Press Tunbridge Wells, Kent [England], 1997)
David Constable illustrates simple projects to show how easy it is to make beautiful classic candles, spiral candles, coloured candles, container candles, perfumed flower candles and floating candles.